Meningkatkan Keputusan Pembelian Shampo Melalui Kesadaran Merek - Safitri Putri Derajat (Desanta Publisher, 2024)
To build brand awareness for Sunsilk Shampoo, improvements can be made in advertising creativity and product quality, which can ultimately enhance consumer purchase decisions. This study aims to examine the influence of advertising creativity and product quality on brand awareness and purchase decision. The research was conducted in Serang City with a purposive sampling of 80 respondents, based on 5 x 16 indicators. Data analysis utilized a SEM approach processed through SmartPLS. The hypothesis testing results indicate that advertising creativity and product quality have a positive and significant direct effect on both brand awareness and purchase decision. Brand awareness has also been shown to have a positive and significant direct effect on purchase decision.